EFL STUDENT-TEACHERS’ ANXIETY DURING FIELD TEACHING PRACTICE - Jannah, Miftakhul; Nurfaidah, Sitti; Halim, Abdul (Journal of English Literature and Linguistic Studies, 2023)
Field teaching practice is an obligatory task for student teachers. Some issues might occur throughout the program commencement, including student teachers’ anxiety. In an attempt to investigate student teachers’ anxiety during field teaching practice, this research was conducted. This study aimed to find out the sources of teaching anxiety EFL student teachers encountered during their field teaching practice. For this purpose, 22 EFL student teachers completing their teaching practicum at assigned schools participated by filling out reflection sheets. Participants’ reflections were then analysed thematically. The findings of the study indicate that the significant source of student teachers’ anxiety comes from lack in interpersonal skills. This study implies that EFL student-teachers should know the source of anxiety and how to deal with it before their real teaching takes place.